1985
DOI: 10.1007/bf00431795
|View full text |Cite
|
Sign up to set email alerts
|

Initial study of methylclonazepam in generalized anxiety disorder

Abstract: The anxiolytic activity of methylclonazepam was compared to lorazepam and placebo in a double-blind, randomized cross-over study, using a latin square design, in 18 inpatients meeting Research Diagnostic Criteria for Generalized Anxiety Disorders. Patients presented at least 1 year of symptomatology and had a minimum score of 20 on the Hamilton Anxiety Scale, despite chronic anxiolytic pharmacotherapy. Daily dosage was flexible, from three to six tablets of methylclonazepam 1 mg, lorazepam 2.5 mg, or placebo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The adverse drug effects can be reversed by co-administration with flumazenil (9). As an anxiolytic, Ansseau et al (5) report a potency three times that of Svante Vikingsson and Ariane Wohlfarth contributed equally to this manuscript.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The adverse drug effects can be reversed by co-administration with flumazenil (9). As an anxiolytic, Ansseau et al (5) report a potency three times that of Svante Vikingsson and Ariane Wohlfarth contributed equally to this manuscript.…”
Section: Introductionmentioning
confidence: 94%
“…The pharmacology of meclonazepam has been investigated in clinical trials as an anxiolytic (5) and, interestingly, as a schistosomicidal drug to treat the parasitic worms Schistosoma haematobium and Schistosoma Mansori (6,7). Meclonazepam can successfully cure parasitic infections with a single dose of at least 0.3 mg/kg, but clinical tolerance was limited by severe adverse drug effects including drowsiness, dizziness, slurred speech, ataxia, muscle weakness, reduced mental alertness, and lateral nystagmus (7).…”
Section: Introductionmentioning
confidence: 99%
“…Ro 11-3128 (meclonazepam) is an anxiolytic benzodiazepine derivative (Ansseau et al 1985) whose antischistosomal properties were reported in the late 1970s (Pax et al 1978). It was considered as a putative drug lead according to the report of the Scientific Working Group on Schistosomiasis/ TDR/WHO (Cioli 2005).…”
Section: Ro 11-3128mentioning
confidence: 99%
“…Benzodiazepines (BZD), important forensic and clinical toxicology drugs, are widely prescribed for neurological and psychiatric disorders and are also highly abused [1][2][3]. Discovered in the mid-1950s, BZD were designed as pharmacotherapies for anxiety, panic attacks, sleep disorders and epilepsy, and they have been used as myorelaxants during surgical and orthopedic procedures [4,5]. BZD are positive allosteric modulators that enhance the binding affinity of the inotropic γ-aminobutyric acid-A receptor (GABA A ) for GABA, the major central nervous system (CNS) inhibitory neurotransmitter [6,7].…”
Section: Introductionmentioning
confidence: 99%